2020
DOI: 10.1002/ecy.2971
|View full text |Cite
|
Sign up to set email alerts
|

Trait–environment interactions affect plant establishment success during restoration

Abstract: Establishment and persistence are central to community assembly and are determined by how traits interact with the environment to determine performance (trait–environment interactions). Community assembly studies have rarely considered such trait–environment interactions, however, which can lead to incorrect inferences about how traits affect assembly. We evaluated how functional traits, environmental conditions, and trait–environment interactions structure plant establishment, as a measure of performance. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 51 publications
4
49
0
Order By: Relevance
“…an interaction between LNC, WDMC, SOM and pH on individual survival at the species level) involving the survival and growth models at both the species and individual levels (Tables 1, S2-S5). Two-way (one trait 9 one environment) interactions had been reported to affect individual survival probability (Laughlin et al, 2018), seedling establishment (Zirbel & Brudvig, 2020) and multiple demographic rates (Blonder et al, 2018). With the inclusion of three-way interactions between two traits and one environment, Worthy et al (2020) found alternative functional designs and multiple growth peaks and they shifted along environmental gradients.…”
Section: Discussionmentioning
confidence: 99%
“…an interaction between LNC, WDMC, SOM and pH on individual survival at the species level) involving the survival and growth models at both the species and individual levels (Tables 1, S2-S5). Two-way (one trait 9 one environment) interactions had been reported to affect individual survival probability (Laughlin et al, 2018), seedling establishment (Zirbel & Brudvig, 2020) and multiple demographic rates (Blonder et al, 2018). With the inclusion of three-way interactions between two traits and one environment, Worthy et al (2020) found alternative functional designs and multiple growth peaks and they shifted along environmental gradients.…”
Section: Discussionmentioning
confidence: 99%
“…We quantified spatial variation in soil moisture within each site half because soil moisture is a key environmental variable that can mediate plant establishment in tallgrass prairies (Grman et al 2015, Zirbel and Brudvig 2020). Soil moisture was measured twice per week during the first growing season in each 25‐m 2 plot using an ML3 ThetaProbe (Dynamax, Houston, TX).…”
Section: Methodsmentioning
confidence: 99%
“…If restoration goals FIGURE 2 | For each step of seed-based wetland restoration, significant revegetation challenges persist and there are numerous opportunities for future research directions. 1 (Broadhurst et al, 2008); 2 (Merritt and Dixon, 2011); 3 (Basey et al, 2015); 4 ; 5 (Suding, 2011); 6 (Butterfield et al, 2017); 7 (Havens et al, 2015); 8 (Hufford and Mazer, 2003); 9 (Broadhurst et al, 2016); 10 (James et al, 2011); 11 (Hess et al, 2019); 12 (Holl and Aide, 2011); 13 (Byun et al, 2013); 14 (Doherty et al, 2011); 15 (Oliver et al, 2015); 16 (Kettenring et al, 2019b); 17 (McKay et al, 2005); 18 (White et al, 2018); 19 (Walck et al, 2011); 20 (Peralta et al, 2017); 21 (Tilley and Hoag, 2006); 22 (Unsworth et al, 2019); 23 (Larson and Funk, 2016); 24 (Zirbel and Brudvig, 2020); 25 (Daniel et al, 2019); 26 (Cleland et al, 2015); 27 (Reinhardt Adams and ; 28 (van Katwijk et al, 2016); 29 (Smith-Cartwright and Chow-Fraser, 2011); 30 (Taddeo and Dronova, 2020).…”
Section: Factors Influencing the Need To Seedmentioning
confidence: 99%